Lapu Lapu ([s.l.] Classic Films, 2003)
Set in the 16th century this is the story of Lapu Lapu, the first Filipino hero, in his battle against Spanish colonizers.
VCD
Producers Florante H. Castillo, Lito Marcos, Mark Lapid, William G. Mayo, Wilson Chua, directed by William G. Mayo
Lito Lapid, Joyce Jimenez, Jeric Raval, Mark Lapid, Roi Vinzon, Jess Lapid
Keywords: Lapu-Lapu.; Heroes--Phils.; Spain--Colonies--Phils.; Feature films